A Soil Monitoring Law for Europe - Panos Panagos; Arwyn Jones; Emanuele Lugato; Cristiano Ballabio (Global Challenges)
Abstract Over 60% of European soils are unhealthy according to the Soil Mission board estimates and the indicators presented in the European Union (EU) Soil degradation dashboard. The situation may worsen if no policy interventions are taken. The unsustainable use of natural resources, in particular the degradation of soils, precipitates biodiversity loss, exacerbated by the climate crisis. In particular, in the EU alone, soil degradation costs over €50 billion per year due to the loss of essential services they provide and to the impact on human health. Here a more precise estimation of the soil degradation cost related to a set of soil degradation processes, ranging between €40.9 and 72.7 billion per year is presented. This newly updated estimate compared to the Impact assessment of the Soil Monitoring Law takes into account the costs of soil erosion, contamination, phosphorus losses, soil carbon losses, nitrogen losses, soil compaction, and soil sealing. However, this estimation might double if it is added to the costs of soil biodiversity loss, floods, droughts, off‐site effects of soil erosion, and health consequences of soil contamination. Therefore, further research is needed to address this knowledge gap and estimate the missing costs. Soil degradation is a critical issue with transboundary implications that requires urgent attention and action at the EU level. The costs of soil degradation are substantial, both in terms of environmental impacts and economic consequences, highlighting the importance of investing in sustainable soil management practices and a harmonized EU soil monitoring system. By addressing soil degradation through the proposed Soil Monitoring Law, investing significant amounts for research and innovation in the Soil Mission, and promoting international cooperation, the EU can take solid steps toward protecting its soil resources and achieving a sustainable future for all.